Pelaksanaan Klinik Sanitasi Untuk Pengendalian Kejadian Ispa Di Wilayah Kerja Puskesmas Palapa Bandar Lampung Tahun 2022: Implementation of a Sanitation Clinic for Controlling Respiratory Tract Infections in the Work Area of the Palapa Health Center in Bandar Lampung in 2022 - Desty Monica Ramadayanti; Retno Pinarsih; Febri Anandita Suralag; Dina Dwi Nuryani; Prima Dian Furqoni; Dias Dumaika (Experimental Student Experiences, 2022)
ISPA is a disease that often occurs in children. WHO estimates that the incidence of ARI in developing countries with under-five mortality rates above 40 per 1000 live births is 15-20% per year in the under-five age group. According to WHO, approximately 13 million children under five in the world die every year, where ARI is one of the main causes of death by killing ± 4 million children under five each year. The results of the pretest and posttest showed that there was a significant change in the participants' pretest and posttest scores, namely the pretest score data had an average increase of 165.5 and the posttest value data had an average increase of 220. This shows that there is a difference in the average score. -the average of participants based on pretest and posttest scores. It is hoped that through this activity it will be able to increase the knowledge, awareness and ability and behavior of the community to create a clean and healthy environment and behavior. So that it can reduce the incidence of ARI and improve environmental health conditions, by educating cadres in the working area of the Palapa Health Center in Bandar Lampung.